THE EFFECTIVENESS OF THE "GUIZZER" LEARNING MEDIA ON THE MATHEMATICAL PROBLEM SOLVING ABILITY OF CLASS V PRIMARY SCHOOL - Lovika Ardana Riswari; Indriyani Ningkrum; Tri Iftitahur Rohmah (Journal of Authentic Research on Mathematics Education (JARME), 2026)
Based on observations and interviews, students' mathematical problem-solving skills were found to be relatively low due to limited understanding of mathematical problems, low learning interest, and the lack of innovative instructional media. This study aimed to investigate the potential of the "Guizzer" learning media to improve the mathematical problem-solving skills of fifth-grade students at SD Negeri Waturoyo. A quantitative pre-experimental approach employing a one-group pretest-posttest design was adopted as an initial exploratory stage of media development, due to the limited sample size, which did not permit the establishment of a control group. Data were obtained through pretests and posttests/data were gathered using pretest and posttest instruments and then analyzed through normality testing, a paired-samples t-test to analyze differences between pre-intervention and post-intervention results, and an N-Gain test to identify the magnitude of enhancement. The normality test the findings revealed that both the pretest data (Sig. = 0.763) and posttest data (Sig. = 0.589) the data followed a normal distribution. Therefore, a paired-samples t-test was conducted. The results showed a significance value of 0.000 (p 0.05), indicating a statistically a significant difference was found between the pretest and posttest scores. Furthermore, the N-Gain analysis yielded a score of 0.5, which falls into the moderate category. The results of this study suggest that the implementation of the "Guizzer" learning media was associated with an increase in students' mathematical problem-solving skills. Therefore, the "Guizzer" learning media demonstrates potential as an instructional tool for developing students mathematical problem-solving skills; however, further studies employing a control-group design are required to provide stronger evidence of its effectiveness.